Measuring antimicrobial prescribing quality in Australian hospitals: development and evaluation of a national antimicrobial prescribing survey tool. (26th February 2015) - James, Rodney; Upjohn, Lydia; Cotta, Menino; Luu, Susan; Marshall, Caroline; Buising, Kirsty; Thursky, Karin
Abstract : The authors describe a tool developed in Australia for collecting qualitative and quantitative data on antimicrobial prescribing in a wide range of hospital settings. This should help hospitals to audit prescribing practices to help achieve the antimicrobial stewardship required for accreditation. Abstract: Objectives: Antimicrobial stewardship (AMS) programmes have been developed with the intention of reducing inappropriate and unnecessary use of antimicrobials, while improving the quality of patient care and locally helping prevent the development of antimicrobial resistance. An important aspect of AMS programmes is the qualitative assessment of prescribing through antimicrobial prescribing surveys (APS), which are able to provide information about the prescribing behaviour within institutions. Owing to lack of standardization of audit tools and the resources required, qualitative methods for the assessment of antimicrobial use are not often performed. The aim of this study was to design an audit tool that was appropriate for use in all Australian hospitals, suited to local user requirements and included an assessment of the overall appropriateness of the prescription. Methods: In November 2011, a pilot APS was conducted across 32 hospitals to assess the usability and generalizability of a newly designed audit tool. Following participant feedback, this tool was revised to reflect the requirements of the respondents. A second pilot study was then performed in November 2012 across 85 hospitals. Results: These surveys identified several areas that can be targets for quality improvement at a national level, including: documentation of indication; surgical prophylaxis prescribed for >24 h; compliance with prescribing guidelines; and the appropriateness of the prescription. Conclusions: By involving the end users in the design and evaluation, we have been able to provide a practical and relevant APS tool for quantitative and qualitative data collection in a wide range of Australian hospital settings.